2016
DOI: 10.1371/journal.pone.0155669
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology of Common Cancers in Southern Iran, 2007-2010: A Cross Sectional Study

Abstract: We have evaluated the ever changing epidemiology of cancers in Fars province, Iran since the re-establishment of Fars cancer registry. Based on the collected data from all related sources in Fars province from 2007–2010 we calculated the cancer age-standardized rates per 100,000 person-years (ASRs). The results are presented as incidence rates of cases by site according to the International Classification of Diseases for Oncology (ICD-O), sex, age, crude rate, and ASRs. In women the total ASR was 41.70 per 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…Also, the annual colon cancer mortality for men and women was 1.54 and 2.46 per 100,000 persons, respectively. Moreover, the mortality rates for colon cancer in the other studies from southern parts of Iran were reported 0.41 and 0.34 per 100,000 persons (1,4,15).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Also, the annual colon cancer mortality for men and women was 1.54 and 2.46 per 100,000 persons, respectively. Moreover, the mortality rates for colon cancer in the other studies from southern parts of Iran were reported 0.41 and 0.34 per 100,000 persons (1,4,15).…”
Section: Introductionmentioning
confidence: 88%
“…Colorectal cancer is one of the major cancers in the world (2). Colorectal cancers (including colon, rectum and anus) are the most common type of gastrointestinal tract cancer and allocate the third rank in men and fourth rank in women in Iran (1,3,4). The annual incidence of this cancer is more than 134,000 new cases and 55,000 deaths are reported annually due to colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The included studies were published from 1968 to 2017. Based on geographical locations, four studies were conducted in all states of Iran [24][25][26][27], three in Fars province [28][29][30], three in East Azerbaijan [15,31,32], two in Ardabil province [33,34], two in Guilan province [35,36], two in Golestan province [37,38], one in Kerman province [39], one in Semnan province [40], one in Tehran metropolis [41], one in Mazandaran province [42], one in Caspian littoral [43] and one in Shahroud city [44]. All the studies have reported ASRs.…”
Section: (A) Description Of Literature Searchmentioning
confidence: 99%
“…The low incidence rate of EC in this province can be attributed to the demographic characteristics of people living in this area, differences in lifestyle, and the presence of other types of risk factors and diseases. In Fars province, other types of cancer such as breast, colorectal, and gastric cancers in women and bladder, prostate and gastric cancers in men have higher incidence rates [30,59,60].…”
Section: Forest Plot Of the Random-effect Meta-analysis For Asrs Ofmentioning
confidence: 99%
“…Colon carcinoma is among the leading causes of cancer-related death throughout the world, with a rising incidence rate in recent years (11). Colon is the site where the greatest density and number of microbes can be found.…”
Section: Introductionmentioning
confidence: 99%